Thalamic nuclei degeneration in multiple sclerosis. (July 2021) - Trufanov, Artem; Bisaga, Gennady; Skulyabin, Dmitry; Temniy, Alexandr; Poplyak, Mariya; Chakchir, Oleg; Efimtsev, Aleksandr; Dmitriy, Tarumov; Odinak, Miroslav; Litvinenko, Igor
Highlights: The decrease in thalamic nuclei volume correlate with the results of EDSS. Patient's with multiple sclerosis have smaller volume of the thalamic pulvinar nuclei. The written section of SDMT is the most suitable cognitive test for MS patients. Abstract: Objectives: To define both the severity and extent of structural alteration in certain thalamic nuclei by means of MR morphometry and to compare these findings with clinical performance in different phenotypes of multiple sclerosis (MS). Methods: We comparatively measured the thalamus nuclei volumes of patients with remitting-relapsing (RRMS) and secondary-progressive (SPMS) phenotypes of multiple sclerosis and healthy control subjects (HC). The evaluation of neurological performance was based on the results of Expanded Disability Status Scale and Multiple Sclerosis Severity Scale. Cognitive and mental state was rated according to the results of Mini-Mental State Examination, Frontal Assessment Battery, Montreal Cognitive Assessment and Symbol Digit Modalities Test. Freesurfer 6.0 was used for thalamic nuclei volumes calculation. Results: The median volume decline in thalamic pulvinar nuclei in RRMS group on the left side (anterior nucleus − 186, 6 mm 3, posterior nucleus – 149, 4 mm 3, medial nucleus 852, 4 mm 3 ) compared to HC (anterior nucleus – 229, 2 mm 3, posterior nucleus – 187, 5 mm 3, medical nucleus – 1081, 3 mm 3 ). Same group, right side – anterior nucleus – 219, 5 mm 3, posterior nucleus 187, 1 mm 3, medial nucleus – 989, 6 mm 3 ; HC group – anterior nucleus 261, 1 mm 3, posterior nucleus 240, 5 mm 3, medial nucleus – 1196, 7 mm 3 (p < 0, 05). The highest correlation of the written section of SDMT was observed with the left ventral anterior nucleus (r = 0, 71). Conclusion: These findings indicate the credible correlation between clinical progression of neurological and cognitive impairment in MS patients with asymmetry left-sided thalamic nuclei atrophy and may be considered a potential predicting tool of MS progression.